FROM ANCESTRAL PORTRAITS TO THE YIN WORLD: VISUALIZING MEMORY AND RECONCILIATION IN AMY TAN’S THE HUNDRED SECRET SENSES - Joseph, Nicy; Ramaswamy, Shobha (ShodhKosh: Journal of Visual and Performing Arts, 2026)
In The Hundred Secret Senses, Amy Tan blends memory, supernatural faith, and the reconciliation of emotions in a way that does not give rigid lines between realism and the fantastic. This result will argue that the utilization of the ghost stories and spiritual memory used by Tan is not only a cultural motif but also a visual cultural and narrative strategy whereby the identity, affect, and healing are constructed. Based on the Memory Studies, the analysis shows how personal, lineal, and collective memories that are passed through spectral storytelling function as a means of emotional attachment and reconciliation. At this point, the fact that Kwan believes in the Yin world and has strong memories of what she believed to be a previous life distorts the lines between the living and the dead and the remembered and imagined. These spectral stories serve as living archives of ancestral memory and parallel visual culture, such as images of ancestors, spirit images, and colour practices, as part of Chinese cultural aesthetics. Through the process of turning memory into a sensory and visual experience, Tan is able to blend myth, folklore, and her own history to make storytelling an act of visual cultural negotiation of loss, guilt and estrangement of emotion, specifically between Kwan and her half-sister Olivia. It is ultimately implied in the novel that emotional healing and self-understanding come about in the process of uniting the spiritual, cultural, and personal memory. This result places The Hundred Secret Senses in the context of memory and trauma, visual culture, and identity as discussed in Chinese American literature.